Green and Ultrasound-Assisted Synthesis of 1,3-Diaryl-2-Propenones Catalyzed by Amberlyte IRA-410 and Amberlyte IRA-400 basic Resins - Masmoudi, Nihel; Chtourou, Manef (Letters in Organic Chemistry, 2023)
This research paper presents a green, safe and easy synthesis of trans-chalcones under ultrasound irradiation in the presence of anionic resins. Several trans-Chalcones have been obtained following an environmentally friendly methodology using Amberlyte IRA-410 and Amberlyte IRA-400 resins as heterogeneous and efficient catalysts. The products of the condensation reaction were generally synthesized in good yields and the analysis confirmed their structures well.
Keywords: Amberlyte IRA-400